2012
DOI: 10.1093/annonc/mds169
|View full text |Cite
|
Sign up to set email alerts
|

The impact of menopause on bone, zoledronic acid, and implications for breast cancer growth and metastasis

Abstract: Recent data from the AZURE, ABCSG-12, and ZO-FAST clinical trials have challenged our understanding of the potential anticancer activity of zoledronic acid (ZOL). Although the results of these studies may appear to be conflicting on the surface, a deeper look into commonalities among the patient populations suggest that some host factors (i.e. patient age and endocrine status) may contribute to the anticancer activity of ZOL. Indeed, data from these large clinical trials suggest that the potential anticancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 108 publications
1
17
0
Order By: Relevance
“…12,13 This led to the hypothesis [11][12][13] that treatment is of benefit only in patients with low concentrations of reproductive hormones (ie, those who are postmenopausal or undergoing ovarian suppression therapy). [14][15][16] To help clarify whether adjuvant bisphosphonates reduce the risk of bone and other metastases, and whether menopausal status affects efficacy, we undertook collab orative meta-analyses of all unconfounded randomised trials that compared breast cancer outcomes in those allocated adjuvant bisphosphonate versus those who were not.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 This led to the hypothesis [11][12][13] that treatment is of benefit only in patients with low concentrations of reproductive hormones (ie, those who are postmenopausal or undergoing ovarian suppression therapy). [14][15][16] To help clarify whether adjuvant bisphosphonates reduce the risk of bone and other metastases, and whether menopausal status affects efficacy, we undertook collab orative meta-analyses of all unconfounded randomised trials that compared breast cancer outcomes in those allocated adjuvant bisphosphonate versus those who were not.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, oral clodronate, when given as adjuvant therapy over 5 years, was shown to significantly reduce the rate of bone metastasis in women with breast cancer receiving standard treatment [115] , [119] . Although one clinical trial reported that clodronate had no effect on metastases and even a negative effect on survival [118] , [120] , bisphosphonates have been widely adopted in clinical practice [121] , [122] based on further positive outcomes from studies with zoledronic acid [123] , [124] , [125] , [126] , [127] , [128] , [129] , [130] , [131] , [132] , [133] , [134] and ibandronate [135] , [136] suggesting that bisphosphonates limit the progression of breast or prostate cancer in bone and other tissues [104] , [114] .…”
Section: The ‘Vicious Cycle’ Of Metastatic Tumour Growth In Bonementioning
confidence: 99%
“…However, in women who are postmenopausal, either naturally (8,10,11) or induced by goserelin (9), a consistent improvement in both DFS and OS with administration of adjuvant bisphosphonates has emerged. The biologic rationale for these observations is an area of intense study (12,13). The interaction between menopause and effects of bisphosphonates is suggested to be linked to the TGFb family (13).…”
Section: Introductionmentioning
confidence: 99%